Mammalia (De Gruyter, 1936)
Mammalia is a peer-reviewed journal devoted to the inventory, analysis and interpretation of Mammalian diversity. It publishes original results on all aspects of systematics (comparative, functional and evolutionary morphology; morphometrics; phylogeny; biogeography; taxonomy and nomenclature), biology, ecology and conservation of mammals.